Relación de los estilos de Crianza con el Autoconcepto de los niños y niñas del nivel de Educación Inicial de la Institución Educativa N° 217 - Aguas Verdes. - Cadillo Espinoza, Karina Enriqueta (2009)
The investigation (research) named Relation of the styles of upbringing with the autoconcept of the children and girls of the level of initial education of the educational institution N° 217 - Green Waters, there had for aim (lens) determine the relation of the styles of upbringing with the autoconcept of the children and girls of the Level of initial Education of the Educational lnstitution N ° 217 – Green Waters in the year 2008. Orientated to achieving this aim (lens), there is hipotetizado that the styles of upbringing relate significantly to the autoconcept of the children and girls of the Level of lnitial Education of the Educational lnstitution N ° 217 - Green Waters in the year 2008. The information has been gathered of 20 children I aces and 20 parents, using as instruments a scale of styles of upbringing and a questionnaire of evaluation of autoconcept. The obtained information has been tried by means of descriptive statistics and inferencial. The contrastación of hypothesis has been carried out by means of the comparison of t - student, determining the following thing: The democratic style of upbringing relates significantly to the autoconcept of the children and girls of the Level of lnitial Education of the Educational lnstitution N ° 217 - Green Waters in the year 2008. The authoritarian style of upbringing relates significantly in a negative way to the autoconcept of the children and girls of the Level of lnitial Education of the Educational lnstitution N ° 217 - Green Waters in the year 2008. The permissive style of upbringing relates significantly in a negative way to the autoconcept of the children and girls of the Level of lnitial Education of the Educational lnstitution N ° 217 - Green Waters in the year 2008.